Disruptions to number bisection after brain injury: Neglecting parts of the Mental Number Line or working memory impairments? - Storer, L; Demeyere, N (Academic Press Inc., 2014)
The aim of this study was to investigate the mechanisms underlying consistent directional number bisection bias in a chronic neuropsychological sample, not selected based on behaviour or lesion definitions. Patients completed a test battery that included measures of number bisection, line bisection, verbal working memory, visual-spatial working memory, egocentric neglect and allocentric neglect. Neither the neglect nor working memory measures were found to significantly correlate with number bisection. Furthermore, when outlier patients with very distinct number bisection biases were compared to patients who did not show any number bisection difficulties, no differences were found between the two groups on any of the other behavioural measures. We conclude that number bisection difficulties are not consistently based on any single deficit, be it neglect or working memory, and biases in number bisection should not be assumed to directly reflect problems in either of these areas.